Henry Wadsworth Longfellow - Longfellow, Henry Wadsworth, 1807-1882.; Schoonmaker, Frances, 1941-; Wallace, Chad (New York : Sterling Pub., 1998)
An illustrated selection of twenty-seven complete or excerpted poems by the renowned nineteenth-century New England poet. Also includes information about his life.
Includes index.
Keywords: Children's poetry, American; American poetry